KETERAMPILAN MENYIMAK : PENGARUH MODEL INDUKTIF BERBANTUAN VIDEO ANIMASI PADA SISWA KELAS V SD - Fitria Anggaraini; Iful Rahmawati Mega; Nurjanah (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This research stems from the low listening skills of fifth-grade students at SD Muhammadiyah Pangkalpinang, which are largely caused by the lack of variety in teaching models and learning media. Such conditions make students less focused and easily bored during learning activities. Therefore, this study aims to examine the effect of applying the Inductive Learning Model combined with the animated video “Pada Zaman Dahulu” on improving students’ listening skills.The study employed a quantitative approach with a Quasi-Experimental design (Nonequivalent Control Group Design) and used the purposive sampling technique. The participants consisted of two classes: an experimental class with 28 students and a control class with 25 students. The learning process was carried out over four sessions using an essay test on listening skills that had been validated and proven reliable. Data were analyzed using normality and homogeneity tests, followed by an Independent Sample t-test with the assistance of SPSS version 26. The findings revealed a significant improvement in the listening skills of the experimental class. The average pretest score increased from 50.93 to 77.79 in the posttest, while the control class increased from 42.36 to 54.52. The result of the Independent Sample t-test showed a Sig. (2-tailed) value of 0.000 < 0.05, indicating a significant difference between the two groups. Thus, it can be concluded that the Inductive Learning Model assisted by the animated video “Pada Zaman Dahulu” has a positive and significant effect on improving the listening skills of fifth-grade students at SD Muhammadiyah Pangkalpinang.